Gambaran Capaian Imunisasi Dasar dan Lanjutan Sebelum, Selama dan Saat Transisi Pandemi COVID-19 di Wilayah Puskesmas Kecamatan Cempaka Putih - Stefanus Gardino Setyo D; Yohanes Firmansyah; Murni L Naibaho (Pusat riset dan Inovasi Nasional, 2023)
Immunization is an action that provides immunity to individuals so that when exposed to a disease they will only experience mild illness or no pain. Immunizations are carried out mainly in children. Immunizations carried out on children are basic immunization and advanced immunization. Due to the COVID-19 pandemic, immunization cannot run properly. This study aims to find out about the achievements of basic and follow-up immunizations between before, during, and the transition period of the COVID-19 pandemic in the Cempaka Putih sub-district. Research Methods: This research is an observational descriptive study in the work area of the Cempaka Putih District Health Center. The research sample in this study was a history of basic and follow-up immunizations from children living in the working area of the Cempaka Putih District Health Center. The results showed that the achievement of basic immunization and children under two in 2019 (before the COVID-19 pandemic) reached the target, then in 2020 (pandemic COVID-19) the achievement of basic immunization and children under two did not meet the target. In 2021 (COVID-19 pandemic) the achievement of basic and under-five immunizations reached the target, then in 2022 (COVID-19 transition period) the achievement of basic and under-five immunizations was achieved.